Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2196/24073
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Language Processing–Based Virtual Patient Simulator and Intelligent Tutoring System for the Clinical Diagnostic Process: Simulator Development and Case Study

Abstract: Background Shortage of human resources, increasing educational costs, and the need to keep social distances in response to the COVID-19 worldwide outbreak have prompted the necessity of clinical training methods designed for distance learning. Virtual patient simulators (VPSs) may partially meet these needs. Natural language processing (NLP) and intelligent tutoring systems (ITSs) may further enhance the educational impact of these simulators. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Among the adaptations that led to such learning opportunities are the clinical case discussions, role-playing of clinical cases, using the medical simulation center, and, to a lesser extent, the use of the web-based clinical simulated patient (DxR ® ). Furlan et al 25 and Kiesewetter et al 26 reported that clerkship students can benefit from similar web-based case discussion software in increasing their clinical reasoning skills, especially during crises times and impossibility of training on real patients. Furthermore, a scoping review by Park et al 27 showed that most clinical competencies could be learned online or in the virtual setting, which supports the usefulness of our implemented adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Among the adaptations that led to such learning opportunities are the clinical case discussions, role-playing of clinical cases, using the medical simulation center, and, to a lesser extent, the use of the web-based clinical simulated patient (DxR ® ). Furlan et al 25 and Kiesewetter et al 26 reported that clerkship students can benefit from similar web-based case discussion software in increasing their clinical reasoning skills, especially during crises times and impossibility of training on real patients. Furthermore, a scoping review by Park et al 27 showed that most clinical competencies could be learned online or in the virtual setting, which supports the usefulness of our implemented adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…This section provides a synthetic description of the main features underlying Hepius's diagnostic model, which is necessary for the full comprehension of the learning analytics. A detailed description of the program is provided elsewhere [23].…”
Section: Diagnostic Process Simulator Componentsmentioning
confidence: 99%
“…We recently developed a VPS, Hepius, which integrates ITS components [23] that address 2 main activities carried out by a physician when managing a patient: data gathering and data analysis. NLP techniques were used to mimic physician-patient interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, deep learning and AI have been integrated into the development and application of ITS for health education purposes. For instance, Furlan et al ( 51 ) developed a virtual patient simulators (VPS) system that allowed students to gather clinical information from the patient's medical history, physical exam, and investigations and allowed them to formulate a differential diagnosis by using natural language. The VPS is also an ITS that provided real-time step-by-step feedback to the student and suggests specific topics the student has to review to fill in potential knowledge gaps.…”
Section: Recommendationsmentioning
confidence: 99%